Bhinneka Tunggal Ika in the Frame of Huma Betang's Philosophy - Herman, Herman; Noor, Ady Ferdian; Rusmaniah, Rusmaniah; Mustikaningsih, Wening (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: Indonesia is rich in diversity, which is caused by the spread of the population across many islands, so it has many differences in religion, ethnicity, race, and culture. The large number of differences will be vulnerable to division and intimidation. Aim: This research aims to integrate the values of the Huma Betang philosophy which is also embodied in the Bhinneka Tunggal Ika frame. This research uses a qualitative descriptive and literature study approach where researchers collect data from various literature sources and journals. Results and Dıscussion: The results of the research show that the philosophy of Huma Betang has the same meaning as the five precepts that Huma Betang has meaning 1) Belief in the Almighty God or Religious Values (Hatala) Dayak people believe in the existence of God; 2) Just and Civilized Humanity, the Value of Justice and Belom Bahadat which has the meaning of life must be fair to all God's people and have good manners; 3) Indonesian Unity or called Handep Hapakat & Isen Mulang, namely the spirit of cooperation and the spirit of never giving up; 4) Democracy led by the wisdom of decisions in representative deliberations, Hapakat Basara & Hupungkal Lingu Nalatai Hapangajan Karendem Malempang means uniting in resolving a problem by consensus so that everything can reach a common agreement; 5) Social Justice for all Indonesian People, also called Belum penyang hinje simpei or living in harmony and peace for the sake of shared prosperity. Conclusion: Huma Betang's philosophy has values that are relevant to Bhinneka Tunggal Ika, which is contained in the motto and ideological foundation of the Indonesian state. In the Huma Betang philosophy, it has the same meaning as the five precepts contained in Pancasila.